THE ASSOCIATION BETWEEN PHYSICAL MOBILITY AND INCIDENT COGNITIVE IMPAIRMENT IN OLDER PUERTO RICAN ADULTS. (11th November 2018) - Barba, C; Dávila-Roman, A; Andel, R; Markides, K; Crowe, M
Abstract: Worse physical performance using a variety of different measures has been associated with greater risk of cognitive impairment and dementia. We examined whether physical mobility measured at baseline is associated with incident cognitive impairment at four-year follow up in a sample of older Hispanic adults. Participants included 2, 199 community-dwelling older adults aged 60+ years from the Puerto Rican Elderly: Health Conditions (PREHCO) Study without cognitive impairment at baseline. Cognitive function was measured using the minimental Cabán (MMC) at baseline and follow up. Physical mobility was measured by the Timed Up and Go Test (TUG). Performance was classified as "slow" for the lowest quartile of speed. Covariate-adjusted logistic and linear regression models were used to examine incident cognitive impairment and decline, respectively. Slow physical performance was associated with an increased risk of incident cognitive impairment. This association remained significant after controlling for age, years of education, gender, depressive symptoms, body mass index, and self-rated health (OR = 1.615; 95% CI = 1.096, 2.379, p<.05). In covariate-adjusted models, lower TUG scores were also predictive of greater cognitive decline over a four-year period (p<.01). Slowed physical mobility may be an early marker for risk of cognitive impairment. Our findings add to evidence that the TUG is a simple and low cost measure that may be useful for identifying older adults who are at risk of cognitive decline and cognitive impairment across diverse populations.